Stimulation of Arabidopsis thaliana Seed Germination at Suboptimal Temperatures through Biopriming with Biofilm-Forming PGPR Pseudomonas putida KT2440 - Pandey, Chandana; Christensen, Anna; Jensen, Martin N P B; Rechnagel, Emilie Rose; Gram, Katja; Roitsch, Thomas (Plants (Basel, Switzerland), 2024)
This study investigated the germination response to temperature of seeds of nine Arabidopsis thaliana ecotypes. They are characterized by a similar temperature dependency of seed germination, and 10 °C and 29 °C were found to be suboptimal low and high temperatures for all nine ecotypes, even though they originated from regions with diverse climates. We tested the potential of four PGPR strains from the genera Pseudomonas and Bacillus to stimulate seed germination in the two ecotypes under these suboptimal conditions. Biopriming of seeds with only the biofilm-forming strain Pseudomonas putida KT2440 significantly increased the germination of Cape Verde Islands (Cvi-0) seeds at 10 °C. However, biopriming did not significantly improve the germination of seeds of the widely utilized ecotype Columbia 0 (Col-0) at any of the two tested temperatures. To functionally investigate the role of KT2440's biofilm formation in the stimulation of seed germination, we used mutants with compromised biofilm-forming abilities. These bacterial mutants had a reduced ability to stimulate the germination of Cvi-0 seeds compared to wild-type KT2440, highlighting the importance of biofilm formation in promoting germination. These findings highlight the potential of PGPR-based biopriming for enhancing seed germination at low temperatures.
Keywords: temperature; beneficial microbe; ecotypes; biostimulant; arabidopsis; rhizobacteria; biofilm; biopriming; germination